First clinical and immunogenicity results including all subjects enrolled in a phase I study of Nous-209, an off-the-shelf immunotherapy, with pembrolizumab, for the treatment of tumors with a deficiency in mismatch repair/microsatellite instability (dMMR/MSI) - Fakih, Marwan; Le, Dung T.; Pedersen, Katrina Sophia; Shields, Anthony Frank; Shah, Manish A.; Mukherjee, Sarbajit; Delaite, Patricia; Faivre, Théa; D'Alise, Anna Morena; Leoni, Guido; Cotugno, Gabriella; Langone, Francesca; et al. (Journal of clinical oncology, 2022)
2515Background: Defective DNA mismatch repair (dMMR) leads to high levels of microsatellite-instability (MSI-H) and insertions or deletions in coding regions, triggering the generation of tumor-specific frameshift peptides (FSPs). We selected 209 shared FSPs among subjects with dMMR/MSI-H cancers, to generate an off-the-shelf vaccine for the treatment of dMMR/MSI-H tumors. Those FSPs were cloned into four proprietary Great Apes Adenoviral (GAd) and four Modified Vaccinia Ankara (MVA) vectors to create a polyvalent viral vectored vaccine named Nous-209 [Leoni, G. et al. Cancer Res, 2020. 80(18): p. 3972-3982.]. Methods: This phase 1 first in human (FIH) study (NCT04041310) evaluates safety and tolerability of two dose levels of the Nous-209 in combination with pembrolizumab, assesses immunogenicity and detects preliminary evidence of anti-tumor activity. Nous-209 is administered intramuscularly, concomitantly with pembrolizumab: one prime (GAd-209-FSP) at the 2nd pembrolizumab infusion and three boosters (MVA-209-FSP) at subsequent infusions each 3 weeks apart. The study is composed of two sequential cohorts i.e. dose escalation and dose expansion. Results: All evaluable subjects with 1st- or 2nd-line metastatic dMMR/MSI-H colorectal (CRC), gastric or gastroesophageal junction (GEJ) cancers enrolled in this phase I (n = 20) were evaluated as of February 03, 2022. Three subjects enrolled in dose level (DL) 1 (2 CRC and 1 GEJ cancer) showed durable confirmed partial responses (PRs). In DL 2 (12 CRC and 5 gastric cancers), 7 subjects had PRs, 6 had stable disease (SD) and 4 had progressive disease (PD) as best response. Most progressors progressed at the 1st CT and none of the responders have progressed. The median follow-up for subjects in DL1 is 24.7 months (22.3-26.7), and 7.6 months (0.9-19.4) in DL 2. The median progression free survival (PFS) and median duration of response (DoR) have not been reached. No dose limiting toxicities (DLTs) were observed. Vaccine immunogenicity was demonstrated in periphery by ex-vivo interferon-gamma ELISpot in 67% of subjects in DL 1, and 82% of subjects with evaluable samples in DL 2. The intratumoral TCR repertoire on pre/post tumor biopsies was analyzed in 3 evaluable subjects with PR and in 1 with PD: expansion and diversification of T cells post treatment with Nous-209 was noted only for the former. Vaccine-reactive TCR clones infiltrating the tumor biopsy post treatment were found in the only subject evaluated to date, with a long-term response. Conclusions: The combination of the Nous-209 and pembrolizumab is safe and well tolerated, and shows signs of clinical efficacy. Nous-209 elicits a neoantigen-specific T cell response expanding within the tumor, possibly contributing to the clinical outcome. Clinical trial information: NCT04041310.